2009
DOI: 10.5012/bkcs.2009.30.8.1749
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Free Imidazolium-Based Ionic Liquids with a Phosphorous-Containing Anion as Potential CO2Absorbents

Abstract: Solubilities of carbon dioxide (CO2) in a series of fluorine-free room temperature ionic liquids (RTILs), dialkylimidazolium dialkylphosphates and dialkylimidazolium alkylphosphites, were measured at 313∼333 K and pressures up to 5 MPa. Henry's law coefficients as the solubility parameter of CO2 in RTILs were derived from the isotherm of fugacity versus CO2 mole fraction. The CO2 solubility in a phosphorus-containing RTIL was found to increase with the increasing molar volume of the RTIL. In general, dialkylim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The CO 2 solubility in the aqueous MEA-[TBP][MeSO 3 ] sample was carried out based on the isochoric saturation method [17]. A high-pressure equilibrium cell (EC) with a capacity of 15 mL made of stainless steel was used to carry out the experiments.…”
Section: Solubility Of Co 2 In Aqueous Mea-[tbp][meso 3 ]mentioning
confidence: 99%
“…The CO 2 solubility in the aqueous MEA-[TBP][MeSO 3 ] sample was carried out based on the isochoric saturation method [17]. A high-pressure equilibrium cell (EC) with a capacity of 15 mL made of stainless steel was used to carry out the experiments.…”
Section: Solubility Of Co 2 In Aqueous Mea-[tbp][meso 3 ]mentioning
confidence: 99%
“…The IL (BMIM)(DBP) was selected due to its miscibility with water and its CO 2 capture capacity, which is comparable to 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ((BMIM)(Tf 2 N)). It was suggested that the longer alkyl chain in the dibutylphosphate anion creates a larger free volume to accommodate more CO 2 molecules [ 11 , 12 ]. The relationship between the physical solubility of gases in other ILs and the free volume of ILs was intensively discussed in Hu et al and Shannon et al [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the membrane resistance R MEMB was calculated from the F P value of the virgin membrane and the resistance values attributable to the ILs were derived from the corresponding F P values once R MEMB was known. According to the figures in Table 2 [62][63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%